Karakteristik Pemerintah Daerah dan Financial Distress: Pendekatan Moderasi Opini Audit sebagai Deteksi Dini Fiskal - Kusumawati, Annisa Fitriana; Nursiam, Nursiam; Sofi, Putri Linggasari; Rahardi, Rafi Amani Muflih; Satriatama, Kenji; Ferdyamin, Pinnacle; Setiawan, Ahmad Syihan (Journal of Business and Economics Research (JBE), 2025)
The urgency of this research stems from the Covid-19 pandemic which has caused health and economic challenges in many countries. This crisis has caused local governments to be in distress, where the initial signs of financial distress in local governments are very important for several reasons. Audit opinions issued by external auditors such as the BPK can provide a clear picture of the financial condition and transparency of budget management at the local government level. Therefore, the objectives of this study are (1) To analyze the relationship between local government characteristics and financial distress (2) To find empirical evidence regarding the impact of whether audit opinions can be an early signal of financial distress. The research method used is quantitative using multiple linear regression to test the effect of local government characteristics on financial distress, in addition to using moderation interaction analysis to determine the role of audit opinion as a moderator variable. The data used are financial reports of companies in the infrastructure, utilities, and transportation sectors in 2020-2023 with data processing using SPSS version 26. The results of the study indicate that financial dependence and service solvency do not have a significant effect on financial distress, while regional independence, poverty, and local revenue have a significant effect. High regional independence and PAD tend to reduce the risk of financial distress, while high poverty rates increase the risk. Audit opinions were found to moderate the relationship between regional independence and financial distress, but did not moderate the relationship between service solvency or other variables with financial distress. These findings emphasize the importance of increasing fiscal independence and PAD management as well as poverty alleviation as a strategy to maintain regional financial stability.